Can Gender Constitute a Modifying Circumstance in Criminal Law? Some Reflections on Legal Practice in the Spanish Context - López de Zubiría Díaz, Sandra (2024)
This study analyzes whether gender constitutes a modifying circums tance in criminal law. For this purpose, it takes as an example the Spanish case, where in recent decades there has been a change in the criminal policy of the State in favor of a criminal law with a gender perspective, specifically in genderbased violence. The article concludes that the term «gender violence» is appropriate because it responds to the essence of this phenomenon, whose particularities have led to a great impulse to its regulation in the Spanish legal system and in the international context. With a criminal policy of intolerance towards the manifestations of this type of violence, legislation with a gender perspective has been promoted, which has considered appropriate the inclusion of an aggravating modifying circumstance if the criminal acts are committed in a discriminatory manner in relation to gender. Hence, from the analysis of the basis of the aggravating circumstance and the reflections on this modification, its existence is positively valued. However, recourse to the criminal code is never a solution on its own, especially if the problem has a social basis that must be addressed with comprehensive public policies to attack the root of the social problem of gender violence.